Challenges in implementing the zoning system on student admission: effects on academic culture in favourite schools - Hidayat, Ramli Nur (Indonesian Journal of Curriculum and Educational Technology Studies, 2023)
This article aims to describe the implementation of the zoning system in student admissions (PPDB) at favourite schools and its impact on the academic culture of these schools. This research employs a qualitative method. Data collection techniques include interviews, observations, and documentation. The subjects of this study were vice principals in charge of curriculum, teachers, and students. The validity of the data was ensured through source triangulation. The data analysis techniques used in this study involved data reduction, data presentation, and conclusion. The results indicate that: (1) SMA N 1 Pati has implemented the zoning system in PPDB. However, one of the main challenges is the difficulty in identifying outstanding students due to the dominance of the zoning admission route. (2) The implementation of the zoning system has impacted the academic culture at SMA N 1 Pati, leading to lower student interest in learning, a decline in academic performance compared to previous years, and a decrease in students’ politeness towards teachers. To maintain a strong academic culture, SMA N 1 Pati has integrated character education into classroom learning and extracurricular activities. Abstrak Artikel ini bertujuan untuk mendeskripsikan penerapan sistem zonasi dalam Penerimaan Peserta Didik Baru (PPDB) di sekolah-sekolah favorit dan dampaknya terhadap budaya akademik di sekolah-sekolah tersebut. Penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi. Subjek penelitian ini adalah wakil kepala sekolah bidang kurikulum, guru, dan siswa. Keabsahan data dipastikan melalui triangulasi sumber. Teknik analisis data yang digunakan dalam penelitian ini meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa: (1) SMA N 1 Pati telah menerapkan sistem zonasi dalam PPDB. Namun, salah satu tantangan utamanya adalah sulitnya mengidentifikasi siswa berprestasi karena dominasi jalur zonasi. (2) Penerapan sistem zonasi berdampak pada budaya akademik di SMA N 1 Pati, yaitu menurunnya minat belajar siswa, menurunnya prestasi akademik dibandingkan tahun-tahun sebelumnya, dan menurunnya kesopanan siswa terhadap guru. Untuk mempertahankan budaya akademik yang kuat, SMA N 1 Pati telah mengintegrasikan pendidikan karakter ke dalam pembelajaran di kelas dan kegiatan ekstrakurikuler.